Association of regular aerobic exercises and neuromuscular junction variants with incidence of frailty: an analysis of the Chinese Longitudinal Health and Longevity Survey. Issue 2 (1st February 2021) - Zhang, Yu‐Jie; Yao, Yao; Zhang, Pei‐Dong; Li, Zhi‐Hao; Zhang, Pei; Li, Fu‐Rong; Wang, Zheng‐He; Liu, Dan; Lv, Yue‐Bin; Kang, Lin; Shi, Xiao‐Ming; Mao, Chen
Abstract: Background: Candidate genes of neuromuscular junction (NMJ) pathway increased risk of frailty, but the extent and whether can be offset by exercises was unclear. The aim of this study was to investigate the association between aerobic exercises and incident frailty regardless of NMJ pathway‐related genetic risk. Methods: A cohort study on participants from Chinese Longitudinal Healthy Longevity Survey was conducted from 2008 to 2011. A total of 7006 participants (mean age of 80.6 ± 10.3 years) without frailty at baseline were interviewed to record aerobic exercise status, and 4053 individuals among them submitted saliva samples. NMJ pathway‐related genes were genotyped and weighted genetic risk scores were constructed. Results: During a median follow‐up of 3.1 years (19 634 person‐years), there were 1345 cases (19.2%) of incident frailty. Persistent aerobic exercises were associated with a 26% lesser frailty risk [adjusted hazard ratio ( HR ) = 0.74, 95% confidence interval ( CI ) = 0.64–0.85]. This association was stronger in a subgroup of 1552 longevous participants (age between 90 and 111 years, adjusted HR  = 0.72, 95% CI  = 0.60–0.87). High genetic risk was associated with a 35% increased risk of frailty (adjusted HR  = 1.35, 95% CI  = 1.16–1.58). Of the participants with high genetic risk and no persistent aerobic exercises, there was a 59% increased risk of frailty (adjusted HR  = 1.59, 95% CI  = 1.20–2.09). HRs for the risk of frailty increased from the low genetic risk with persistent aerobic exercise to high genetic risk without persistent aerobic exercise ( P trend <0.001). Conclusions: Both aerobic exercises and NMJ pathway‐related genetic risk were significantly associated with frailty. Persistent aerobic exercises can partly offset NMJ pathway‐related genetic risk to frailty in elderly people.